The Representation of Japanese Working Women and the Labor Standard Law of Japan – a Feminist Postcolonial Approach - Rosario, Angela Louise C. (Silva Iaponicarum, 2024)
Since the 1947 Constitution was drafted at the behest of the Allied General Headquarters led by the Supreme Commander of the Allied Powers (SCAP), it is only fitting to scrutinize the media directly under it. One of the policies that should have affected Japanese women’s status is the Labor Standard Law. With this Law as a reference point, this paper anchors the SCAP’s ideals for Japanese women in terms of labor whilst I look at the portrayal of Japanese women in the 1948 issues of Pacific Stars and Stripes, an unofficial military daily newspaper under the supervision of SCAP. Through the lens of feminist postcolonialism with power and propaganda as a framework, I posit that the images of working women published by Pacific Stars and Stripes reinforce the internal contradictions presented by Labor Standard Law, which are accompanied by vivid examples of colonial power plays and the exoticization of Japanese women.